Od Třetího Říma ke „konci dějin“: Ruská filosofie dějin na pomezí sociálních věd a literatury - Miloslav Petrusek (Historicka Sociologie, 2017)
This study provides a brief reconstruction of the Russian philosophy of history, which is even now a relevant part of the Russian political science and political practice. Particularly, the author emphasizes that 1. the Russian philosophy of history can serve as an example showing how other social and cultural wholes are differentiated within the philosophy of history; that 2. in addition to the classical philosophy of history a new approach towards history – often called “the civilization studies” – is now carried through alternating traditional Marxist conception of social and economic formations; that 3. the dominant theme of the Russian philosophy of history is – in contrast to the Western conceptions – the relation of the individual and history; that 4. the Russian philosophy of history is stylistically first and foremost expressed in fiction, metaphorically and figuratively. The author exemplifies his theses in the account of the work of Radiscev, Odoevsky, Dostoevsky, Tolstoy, Aldamov, and Grossman.